Artificial Intelligence in Armed Conflict: Perspectives from International Humanitarian Law (Unity Journal, 2025)
The use of artificial intelligence (AI) in armed conflict gives rise to unprecedented challenges in international humanitarian law (IHL). This article examines the complex relationship between AI and IHL. It focuses on the application of autonomous weapons systems (AWS), cyber warfare, surveillance, and precision targeting. The use of AI has been believed to enhance precision and reduce collateral damage. However, there are some challenges, like the loss of human control over decision-making, the potential for algorithmic bias, and the questions of attribution. These issues threaten the core principles of IHL, that is, distinction, proportionality, and humanity. This article fi nds that AWS, constituting a ‘third revolution in military affairs, consists of a risk of violating the principle of distinction by misidentifying targets because of inherent biases in their programming. Similarly, the research discovers that the use of AI in cyber operations raises concerns about the proportionality of attacks and the difficulties in  attributing responsibility for such operations. This article analyzes these challenges, including insights from case studies and comparative analyses of AI usage in military operations. The study follows a qualitative research methodology and analyzes data collected from primary and secondary sources. By exploring particular events, this research highlights the pressing need for a reconsideration of existing legal frameworks that address the peculiar challenges presented by evolving  technology. Ultimately, this article seeks to contribute to the ongoing discourse on developing ethical and legal frameworks necessary to govern AI’s use in warfare, ensuring compliance with IHL while respecting state sovereignty and national security.